Electronic dictionary production system (EDIPS) - Harihodin, Hezul Hezry (2006)
A dictionary is a reference book containing an alphabetical list of words, with information given for each word, usually including meaning, pronunciation, and etymology. A dictionary is a book composed of an alphabetical listing of words with their meanings. There are general dictionaries of English and other languages and specialized subject dictionaries in fields such as business, law, medicine and many more. In monolingual dictionaries, the words are explained and defined in the same language. In bilingual dictionaries, they are translated into another language. Dewan Bahasa dan Pustaka (DBP) or also known as Institute of Language and Literature Malaysia is the sole agency in Malaysia that is responsible for building, expanding and enriching Bahasa Melayu as the national language in Malaysia. Several steps are involved in producing a dictionary. The steps include â€œPerbahananâ€, â€œPenyenaraianâ€, â€œPengagihanâ€, â€œPendrafanâ€, â€œPenyuntinganâ€, â€œPenyuntingan KAPIâ€ and â€œPenjanaanâ€. An analysis of the current DBP business process, found weaknesses and constraints in the implementation of the current dictionary production processes. The production of a dictionary was time consuming and requires lots of effort. A prototype system of EDiPS was developed and has demonstrated and conclude that analysis can be done effectively and timely. EDiPS enables referencing and sharing of information among users. Generation of dictionary could also be performed in a more effective and flexible manner. The use of EDiPS can reduce the time and cost of dictionary production.